IoT Application: Flood and Water Pollution Monitoring by Using Image Processing - Azahar, Amir (2018)
Early flood Warning Systems are being used in many places, however, this warning systems take times to inform all the residences that staying in the areas where water level above normal to apprise that flood will be happened soon. Flood and water pollution monitoring system can reduce economic losses and reduce the number of deaths from disasters by delivering information which allows citizens and organizations to plan necessary actions for the disaster by quick action. This paper introduced the flood and water pollution monitoring system that supported by Raspberry Pi single computer board to apply the image processing process through the Pi Camera and use the IoT application system for the monitoring from the cloud to the mobile apps through the wireless communication.